2011
DOI: 10.1152/japplphysiol.00330.2011
|View full text |Cite
|
Sign up to set email alerts
|

Depressed contractile performance and reduced fatigue resistance in single skinned fibers of soleus muscle after long-term disuse in rats

Abstract: Long-term disuse results in atrophy in skeletal muscle, which is characterized by reduced functional capability, impaired locomotor condition, and reduced resistance to fatigue. Here we show how long-term disuse affects contractility and fatigue resistance in single fibers of soleus muscle taken from the hindlimb immobilization model of the rat. We found that long-term disuse results in depression of caffeine-induced transient contractions in saponin-treated single fibers. However, when normalized to maximal C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…3) [26]. Udaka et al reported that the decrease in muscle weight due to muscle non-use is accompanied by a decrease in muscle fiber [27]. In this study, a decrease in the size of muscle fibers accompanied by a decrease in gastrocnemius muscle weight was observed following ankle fixation for 2 weeks.…”
Section: Discussionsupporting
confidence: 52%
“…3) [26]. Udaka et al reported that the decrease in muscle weight due to muscle non-use is accompanied by a decrease in muscle fiber [27]. In this study, a decrease in the size of muscle fibers accompanied by a decrease in gastrocnemius muscle weight was observed following ankle fixation for 2 weeks.…”
Section: Discussionsupporting
confidence: 52%
“…possibly due to a loss of thick and thin myofilaments (Hvid et al 2017;Udaka et al 2011) potentially resulting in an altered force-length relationship (i.e. reduced overlap between actin and myosin at longer vs shorter muscle lengths).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Disuse muscle atrophy can be induced experimentally through bandaging [26], receiving a nerve block [27], or having the tail suspended [28]. The nerve block method is useful for studying the pathology of surgical injuries where nerve function is altered.…”
Section: Discussionmentioning
confidence: 99%
“…Tail hanging is an appropriate and effective method used in the absence of weight loading, whilst maintaining skeletal mass and weightless atrophy. Bandage fixation, where artificial immobilization of the limb occurs, is the most widely used method in the study of muscular atrophy [26]. In this study, casting tape was used to fix the limb and induce disuse muscle atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation